Mediating Netherlandish art and material culture in Asia - North, Michael; North, Michael; Kaufmann, Thomas DaCosta; Kaufmann, Thomas DaCosta (Amsterdam studies in the Dutch golden age, 2014)
Cover; Contents; Preface; Introduction: Mediating Cultures / Thomas DaCosta Kaufmann and Michael North; 1. Terms of Reception: Europeans and Persians and Each Other's Art / Gary Schwartz; 2. Reconfiguring the Northern European Print to Depict Sacred History at the Persian Court / Amy S. Landau; 3. Dutch Cemeteries in South India / Martin Krieger; 4. Coasts and Interiors of India: Early Modern Indo-Dutch Cross-Cultural Exchanges / Ranabir Chakravarti; 5. Art and Material Culture in the Cape Colony and Batavia in the Seventeenth and Eighteenth Centuries / Michael North.